Two New Species of Land Leeches from Thailand (Hirudiniformes: Haemadipsidae) - NGAMPRASERTWONG, THONGCHAI; THIRAKHUPT, KUMTHORN; PANHA, SOMSAK (Tropical Natural History, 2007)
Two new species of haemadipsid land leeches from Thailand are described. The first, named Haemadipsa trimaculosa Ngamprasertwong, n. sp., is a ground leech and is distributed in Northeastern and Southern Thailand at low altitude (100-900 m). The second species, named H. crenata Ngamprasertwong, n. sp., is a bush leech and is distributed in Northern and Northeastern Thailand at high altitude (1000-1800 m).